2009
DOI: 10.1103/physrevlett.103.075001
|View full text |Cite
|
Sign up to set email alerts
|

Edge-Localized-Mode Suppression through Density-Profile Modification with Lithium-Wall Coatings in the National Spherical Torus Experiment

Abstract: Reduction or elimination of edge localized modes (ELMs) while maintaining high confinement is essential for future fusion devices, e.g., the ITER. An ELM-free regime was recently obtained in the National Spherical Torus Experiment, following lithium (Li) evaporation onto the plasma-facing components. Edge stability calculations indicate that the pre-Li discharges were unstable to low-n peeling or ballooning modes, while broader pressure profiles stabilized the post-Li discharges. Normalized energy confinement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
147
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(161 citation statements)
references
References 28 publications
(23 reference statements)
13
147
1
Order By: Relevance
“…Subsequent analysis of the MHD stability of these profiles has revealed that the edge plasma is close to the stability boundary for peeling-ballooning modes for the discharges without lithium which exhibit ELMs. However, in the discharges with lithium, the changes in both the edge profile and the resulting equilibrium move the stability boundary away from the experimental values [20]. The source of the increased radiation in the discharges with lithium appears to be metallic impurities, notably iron, while the increase in the Z eff is more attributable to an increase in the carbon impurity content [21].…”
Section: Discussionmentioning
confidence: 87%
“…Subsequent analysis of the MHD stability of these profiles has revealed that the edge plasma is close to the stability boundary for peeling-ballooning modes for the discharges without lithium which exhibit ELMs. However, in the discharges with lithium, the changes in both the edge profile and the resulting equilibrium move the stability boundary away from the experimental values [20]. The source of the increased radiation in the discharges with lithium appears to be metallic impurities, notably iron, while the increase in the Z eff is more attributable to an increase in the carbon impurity content [21].…”
Section: Discussionmentioning
confidence: 87%
“…ELM suppression with lithium coatings was shown to coincide with a shift of the density pedestal away from the separatrix, as well as significant increase in its width. By shifting the peak density gradient away from the separatrix, lithium reduced the bootstrap current at the edge (where it had the largest effect on stability), suppressing ELMs [14,17]. With inclusion of the additional data in Figure 2(a-b), it is now apparent that the density pedestal shifted and widened continuously with increasing lithium deposition, even after ELMs were completely suppressed.…”
Section: Evolution With Increasing Lithiummentioning
confidence: 94%
“…Elements of the first experiment have been described previously [8,9,[14][15][16][17][18][19]; it was the first experiment to use the upgraded dual evaporator LITER lithium deposition system [8,10] and began with an entirely lithium-free baseline. In that experiment, medium triangularity (δ~0.5) discharges with lithium coatings >400 mg and neutral beam power P NBI = 4 MW reached global stability limits and disrupted at ~0.3s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work [26], we compared the profiles and stability of the endpoints of the experiment, i.e., ELMy pre-lithium discharges versus completely ELM-free discharges with thick lithium coatings. The conclusions were that lithium widened the density pedestal and shifted it away from the separatrix, causing similar changes in the edge pressure and current profiles, and that this caused the plasma to be farther from its peeling-ballooning stability boundary, i.e., more stable.…”
Section: Lithium Wall Coatings and Elmsmentioning
confidence: 99%